2019
DOI: 10.1111/jvh.13151
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sustained functional cure in hepatitis B envelope antigen‐negative patients achieving hepatitis B surface antigen seroclearance with interferon‐alpha–based therapy

Abstract: Hepatitis B surface antigen (HBsAg) loss is considered a functional cure in chronic hepatitis B (CHB). However, the durability of HBsAg loss after stopping treatment remains unknown. This study aimed to assess the sustained functional cure achieved by interferon therapy in hepatitis B envelope antigen (HBeAg)‐negative CHB patients. In this prospective study, 176 HBeAg‐negative CHB patients with functional cure were enrolled for 12 weeks of cessation treatment, and treatment information and baseline data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 46 publications
3
38
2
Order By: Relevance
“…No significant difference was found ( p = .14). Finally, previous studies have reported that anti‐HBs positivity or high anti‐HBs levels are a predictor of a sustained functional cure 8,11,19 . Ten studies reported the status of anti‐HBs.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…No significant difference was found ( p = .14). Finally, previous studies have reported that anti‐HBs positivity or high anti‐HBs levels are a predictor of a sustained functional cure 8,11,19 . Ten studies reported the status of anti‐HBs.…”
Section: Resultsmentioning
confidence: 91%
“…Then, after reading the full texts and evaluating them according to the inclusion and exclusion criteria, 108 studies were excluded; 9 studies lacked full‐text articles, 3 had small sample sizes, 25 reported irrelevant outcomes, 41 provided inadequate data on our outcomes, and 30 failed to exclude patients coinfected with HIV, HCV and/or HDV. Finally, 38 full‐text articles were included in this analysis 8‐45 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations